2009
DOI: 10.1074/jbc.m109.062109
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Pathway Suppressor 2 (GPS2) Is a Transcriptional Corepressor Important for Estrogen Receptor α-mediated Transcriptional Regulation

Abstract: We have identified G protein suppressor 2 (GPS2) as a stable component of the SMRT corepressor complexes. GPS2 potently represses basal transcription, with the repression domain mapped to the N-terminal silencing mediator of retinoic acid and thyroid hormone receptor (SMRT)-interacting domain. Knockdown of GPS2 abrogates, whereas overexpression potentiates, SMRT-mediated repression activity. The SMRT complexes are involved in 4-hydroxyl-tamoxifen (4OHT)-mediated gene repression by estrogen receptor ␣ (ER␣). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…Chromatin Immunoprecipitation Assays-MCF-7 cells were treated with 100 nM E2, and ChIP assays were performed according to our published protocol (18) except that ␣-HDAC7, ␣-ACTN4, and ␣-ER␣ antibodies were used.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin Immunoprecipitation Assays-MCF-7 cells were treated with 100 nM E2, and ChIP assays were performed according to our published protocol (18) except that ␣-HDAC7, ␣-ACTN4, and ␣-ER␣ antibodies were used.…”
Section: Methodsmentioning
confidence: 99%
“…Using the ERE-TK-Luc reporter, NCOR2 acted as a corepressor for ERa-mediated transcription (21,22), whereas on the ERE-E1b-Luc reporter, it was shown that NCOR2 was required for full ERa transcriptional activity (20). We therefore used both luciferase reporters in turn to test the modulation of BQ323636.1 on ERa-mediated transcription activation (Fig.…”
Section: Bq3236361 Modulates Era Transcriptional Activation Activitymentioning
confidence: 99%
“…2A). Both NCoR and SMRT form complexes with histone deacetylase 3 (HDAC3), transducin ␤-like protein 1 (TBL1)/TBL1-related protein 1 (TBLR1), and G protein pathway suppressor 2 (GPS2) (22)(23)(24)(25). HDAC3 interacts with the N-terminal SWI3/ADA2/NCoR/ TFIIIB-like domain along with a short upstream sequence.…”
mentioning
confidence: 99%